French Colonialism and Demonstrations in Algeria History of Lions Demonstrations the December 11, 1960 CE as a Model (Flood of National Consciousness) (مجلة الواحات للبحوث والدراسات, 2026)
This Article aims to Highlight the Importance of Freedom of Expression for Both Free and Oppressed Peoples. It is a Right Enshrined in Human Rights Charters and Guaranteed by the Constitutions of Democratic and Liberal States. It is a Manifestation of Modern Civilization and a Right Guaranteed to Peoples Governed by Democratic Systems Worldwide. The Human and Civil Rights were Enshrined after the Success of the French Revolution of (1789 CE), which brought Lofty Ideals for the Citizen, such as Fraternity, Justice, and Equality. The Right to Engage in Public Demonstrations was thus Enshrined as a Legitimate and Fundamental Human Right.The Research Concluded with a Number of Results that Highlighted the Importance of Popular Demonstrations in Defending the Rights of Oppressed Peoples and Demanding their Rights, foremost among them their Freedom and Independence from the Yoke of Hateful Colonialism. The Demonstrations represented a Manifestation of the Solidarity, Unity, and Genuine Patriotism of the Algerian People, who yearned for their Freedom and Independence. This Article Employs Both Descriptive and Comparative Methods.